California Foundations of Education : Educational Development Within a Diverse Social History - Noel, Jana (Myers Education Press, 2020)
As Jana Noel taught courses in Educational Foundations, she was constantly struck bythe lack of attention to the development of education in California within the currently available Educational Foundations textbooks. As she and other teachers worked their way through traditional texts, they began asking their students questions such as the following. How has the unique, diverse social history of California impacted the development of its public schools? Did California have legalized school segregation? Is there anything about the political structure of California that may have an impact oneducation? How many times has California law changed to either allow or ban bilingual education? By simply raising questions such as these, Noel noticed a large increase in interest in what had often been considered dry subjects such as history, educational politics, and educational funding. California Foundations of Education addresses the lack of attention to California'seducation within Educational Foundations textbooks. The ultimate goal of the book is toscrutinize how education in California has developed in relation to the unique, diverse social history of California. Perfect for courses such as: Educational Foundations, Social Foundations of Education, Introduction to Teaching Multicultural Education, Curriculum and Instruction